Reproductive patterns in deep versus shallow populations of the precious Mediterranean gorgonian Corallium rubrum (Linnaeus, 1758) (Sardinia, central-western Mediterranean) - PORCU, C.; FOLLESA, M. C.; CANNAS, R.; CAU, AL.; SOLDOVILLA, G.; PESCI, P.; CAU, AN. (Mediterranean Marine Science, 2017)
This study quantifies the main reproductive features of the long-lived red coral Corallium rubrum, an octocoral endemic to the Mediterranean Sea and neighboring Atlantic areas and one of the most valuable of all marine species, at different depths (38-40 m versus 96-115 m) in north-western Sardinian waters (Central-Western Mediterranean Sea). Different population structures between depths were observed with shallow colonies smaller (in basal diameter and height) than deeper ones. Both populations were all gonochoric at polyp and colony level and fertile. The sex-ratio was balanced in the deep red corals while in the shallow ones it was significantly biased towards female probably in response to perturbations such as mass mortality events more common at shallow levels. Deep and shallow colonies were found to have a synchronous female sexual products development in the two depths investigated. C. rubrum produced large female sexual products in both depth intervals in relationship with its reproductive mode, confirming a long oogenic development. In contrast to reproductive timing, the volume occupied by female sexual products per polyp was different between the populations, being higher in the deep than in the shallow populations. C. rubrum exhibited a reproductive strategy characterized by a relative low number of female sexual products per polyp revealing significant differences among the two depth ranges analyzed with a lower mean value of sexual products in the shallow colonies (mean fecundity per polyp: 1.14) than in the deeper ones (mean fecundity per polyp: 2.09). These results indicate differences in reproductive parameters such as sexual products distribution and reproductive output (fecundity) were observed between shallow and deep populations of C. rubrum, in particular within deep dwelling populations.